Lifecycle deficit and economic support ratio in Nigeria: The national transfer account approach - Onisanwa Idowu Daniel; Yohanna Sule (Journal of Economics and Management)
Aim/purpose – The benefit of changing the population age structure only accrues to an economy if the labor market absorbs the increasing number of the working population at a given labor income that surpasses the prevailing consumption of that age group. However, the prevailing conditions in Nigeria suggest that consumers outweigh producers amidst the increasing working-age share of the population. While the demographic dividend has been established in some advanced countries, the same cannot be said in Nigeria. Thus, this study uses annual data projections by the United Nations to examine the interplay between consumption, labor income, and the economic support ratio in Nigeria between 2001 and 2050.